Rumah Sehat dan Kejadian Diare: Studi di Daerah Pesisir: Healthy Houses and Diarrhea Incidence: A Study in Coastal Regions - Diansafitri, Mutia; Kurnia, Risman; Samosir, Kholilah (Poltekes Kemenkes Tanjungpinang, 2025)
The role of a healthy home and the environment has a significant influence on individual health. Tanjungpinang City is an archipelago area where most of the population lives on the coast. The component of healthy house sanitation is strongly related to the incidence of diarrheal diseases. In 2023, the incidence of diarrhea in Tanjungpinang City was 2273 cases. This research was carried out in an observational, descriptive, and analytical manner, with a cross-sectional research design; the sample in this study consisted of 100 houses of residents living in the coastal area of Tanjungpinang City. The analysis of this study was in the form of a Chi-Square analysis, namely the relationship between the components of healthy home sanitation (clean water facilities, healthy latrine facilities, wastewater disposal facilities, waste management facilities, food and beverage management, and the application of hand washing with soap) and the incidence of diarrhea. This study showed that the management of food and beverages was related to the incidence of diarrhea, and the application of hand washing with soap was related to the incidence of diarrhea. This study concludes that there was a relationship between food and beverage management, the application of hand washing with soap, and the incidence of diarrhea. This research is expected to play an important role and be urgent in developing information and usefulness in solving the problem of healthy homes and control of diarrheal diseases in the coastal areas of Tanjungpinang City, Riau Islands Province.